The first record of Late Jurassic megateuthidid belemnites – Chuvashiteuthis aenigmatica gen. et sp. nov. from the upper Kimmeridgian of Central Russia. - Ippolitov, Aleksei P.; Berezin, Alexander Yu.; Rogov, Mikhail A.; Desai, Bhawanising G. (Czech Geological Survey, Prague, 2017)
Present paper discusses finds of peculiar Upper Kimmeridgian belemnitids from Central Russia. Systematic morphological investigation, combined with biometrical comparison and mineralogical study, has shown that these belemnitids should be classified within the familyMegateuthididae. They are described herein as huvashiteuthis aenigmatica gen.et sp. nov. These finds are the youngest record of megateuthidid belemnites, which are considered to die out during the Bathonian, thus extending the total range of the family by ~ 12Ma. The described species co-occurs with scarce and suppressed Boreal belemnites and abundant ammonites of Boreal-Atlantic and Tethyan affinities, supposing similar origin also for the newly described genus. In addition to new data on belemnites, stratigraphical distribution of remarkable “Laevaptychus-bearing” horizons in the Kimmeridgian and Volgian of the Russian Platform is briefly outlined.
Keywords: Belemnites; Megateuthididae; Chuvashiteuthis aenigmatica gen. et sp. nov.; rostrum; phragmocone; biogeography; Mesozoic::Jurassic::Upper::Kimmeridgian; Мезозой::Юрская::Верхний::Киммериджский